The economic impact of highly pathogenic avian influenza on egg production in Minnesota during the 2014 - 2015 outbreak - Bockelmann, Troy Robert, author; Frasier, W. Marshall, advisor; Koontz, Stephen R., committee member; Magzamen, Sheryl, committee member (Colorado State University. Libraries, 2016)
Highly Pathogenic Avian Influenza (HPAI) outbreak in the United States affected 48 million domestic poultry birds. Minnesota experienced 101 confirmed detections with the majority in the laying hen and turkey populations. This research employs mathematical programming to estimate individual egg producer net returns above transportation costs for each week of the outbreak period and to aggregate these estimates to an industry-level impact. When there is a detection of HPAI the primary government response is to designate control areas around the infected premises. Within these control areas rules are established for culling of poultry and restricting travel. A three kilometer and a ten kilometer “control area” perimeter are standard guideline practices established by USDA-APHIS. A linear programming model is developed and parameterized to calculate returns under a range of control scenarios in the face of the historical outbreak. By updating and solving the model iteratively to represent adaptation to on outbreak across time, results for each time period computed and compared to a base model that represents an uninfected circumstance. The change in net revenue as compared to the base equilibrium scenario quantify the lost benefits that comprise the economic impacts from HPAI. Overall total industry loss for the 14-week outbreak period ranged from $7 million where three kilometer radius control areas were employed to $10 million a ten kilometer regime. Fourteen percent of producers lost less than $10,000 in revenue and approximately 3 percent of the producers lost revenue greater than $1 million. The increase in transportation costs for the three kilometer control area was approximately $25 and approximately $11,000 for the ten kilometer control areas. Preventing the spread of HPAI is important to society. Measures to prevent disease spread are important and need to be enforced. It is important that these additional avoidance and adaptation costs be considered when determining the best implementation of control measures in the face of a disease outbreak.
Keywords: HPAI; egg production; transportation